KCC2 activity is critical in limiting the onset and severity of status epilepticus - Liliya Silayeva; Tarek Z. Deeb; Rochelle M. Hines; Matt R. Kelley; Michaelanne B. Munoz; Henry H.C. Lee; Nicholas J. Brandon; John Dunlop; Jaime L. Maguire; Paul Davies; Stephen J. Moss (2015)
Significance Status epilepticus (SE) is defined as a state of continuous unremitting seizures that often exhibits underlying deficits in neuronal inhibition mediated by GABA A receptors. The efficacy of neuronal inhibition is critically dependent on the activity of the K + /Cl – cotransporter KCC2, which allows neurons to maintain low intracellular Cl – levels. KCC2 activity is enhanced by phosphorylation of residue serine 940, and here we show that SE leads to rapid dephosphorylation of this key regulatory residue. Moreover, we demonstrate that deficits in S940 phosphorylation directly contribute to the onset and severity of SE. Collectively, our results suggest that deficits in KCC2 activity directly contribute to the pathophysiology of SE.